Assessment of Growth Disturbance in Japanese Children with IBD. (5th May 2010) - Shono, Tetsuo; Kato, Mayuko; Aoyagi, Yo; Haruna, Hidenori; Fujii, Tohru; Kudo, Takahiro; Ohtsuka, Yoshikazu; Shimizu, Toshiaki
Abstract : In Japan, there is as yet no report on growth retardation in children with IBD. We therefore investigated the cause of growth retardation in Japanese children with IBD. We investigated the height, body weight, serum levels of albumin, IGF-I, CRP, and cytokines, and the amount of corticosteroid administered in children with Crohn's disease (CD, n = 15 ) and ulcerative colitis (UC, n = 18 ). Our results suggest that growth retardation is already present before the initial visit in children with CD, and chronic inflammation may be responsible this growth disturbance. Moreover, the amount of PSL used may contribute to growth retardation by decreasing the serum levels of IGF-I in children with IBD.